Effects of social media exposure on adolescent sexual attitudes and behavior: A systematic review - Fransiska Imavike Fevriasanty; Bagong Suyanto; Oedojo Soedirham; Rahma Sugihartati; Ahsan Ahsan (Intelektual Pustaka Media Utama, 2021)
Aside from the role of family and peer groups, social media is also one of the major agents of sexual socialization in adolescents. Since it is relatively easy to connect to the internet these days, these people now have a wider access to pornographic content that could trigger them to engage in risky sexual behaviors. This review aimed to provide an analysis of the influence of social media exposure on adolescent’s sexual attitudes and behavior as well as describe limitations of the studies being reviewed. This study was based on several electronic databases namely Google Scholar, Science Direct, Proquest Health and Medical Complete, Proquest Science and Pscycholgy Journals, and PubMed, from 2011 to 2018, which revealed a total of 1351 research articles, with only 21 articles meeting the inclusion criteria and reviews. The result showed higher percentage of studies under reviewed mention the effect of social media exposure are related to sexual attitudes, behaviors, initiation and risks, as well as parental monitoring, academic achievement and gender. Conclusively, it is recommended to educate adolescents about the negative risks of social media exposure on sexual attitudes and behavior, as well as the importance of the role of parental monitoring of restrictions on sexualized media access.